Leadership and System Transformation: Advancing the Role of Community Health Nursing - Josephine Etowa; Ilene Hyman (York University Libraries, 2022)
It is widely recognized that structural and social determinants of health (SDoH) account for a large proportion of health inequities in Canada. According to the Public Health Agency of Canada (PHAC), many health actors are required to provide leadership and direction in tackling health inequities. In this paper we argue that community health nurses (CHNs) are well situated to play a critical role in health system transformation in Canada. CHNs are known for having a holistic and collaborative approach with competencies beneficial for the reduction of health inequities. However, to become more consistently effective advocates of health equity, CHNs require competencies in the principles of equity and social justice, community engagement, communication, coalition building, and system transformation. Having a critical mass of CHNs with appropriate leadership skills in knowledge generation and mobilization, advocacy, and collaboration is fundamental to effectively addressing health inequities in Canada.